An Opportunity to Refocus on the 'Humane' in Experimental Endpoints: Moving beyond Directive 2010/63/EU. Issue 4 (September 2013) - Ashall, Vanessa; Millar, Kate
Humane endpoints are a core refinement concept in animal experimentation. This paper identifies an urgent requirement for individuals and institutions to refocus on humane endpoints as part of the transposition of Directive 2010/63/EU into the national laws of the Member States, and to go beyond their legal construction when setting new guidance or applying humane endpoints in practice. It will be argued that requirements for humane endpoints within the Directive appear not to promote recent advances in best practice, but seem reliant on a narrow and potentially outdated definition of the term. We describe progress that has been made in encouraging change in the construction and application of humane endpoints, and suggest that Directive 2010/63/EU does not sufficiently acknowledge the conceptual complexity of this refinement strategy. For example, a useful development representing recent consensual views of best practice has been proposed by an EU consortium (in 2012). A complex approach to humane endpoints may place additional demands on institutions and raise challenges that would, unfortunately, not need to be overcome in order to remain within the Directive's current requirements regarding humane endpoints. We argue that there is now a need for a practical tool to help structure appropriate ethical reflection during research planning and experimentation, in order to facilitate best practice in the application of this important refinement concept.